Proportion of Specific Factors Risk of Breast Cancer on Women Age 25-65 Years - Girsang, Bina Melvia (Jurnal Keperawatan Soedirman, 2018)
Women who do early detection of breast cancer can be said to be still a little. Though the importance of breast examination since early is to know a woman's breasts under normal circumstances or not. This study aims to determine the proportion of several specific factors that cause the risk of breast cancer incidence in women aged 25-65 years with an observational analytic method with case control design. Sampling is done by using probability sampling with simple random sampling technique approach. The sample size was 23 women in the case group and 46 women in the control group in the working area of Gandus and Dempo, South Sumatera – Palembang sub-districts from May to September 2017. Screening data were collected using a questionnaire and analyzed by bivariate analysis using chi square and fisher's exact statistical tests, continued with multivariate analysis using multiple logistic regression statistic test. Based on the results of bivariate analysis found that there are 7 specific risk factors from the overall 15 related factors (p value <0.05) with risk factors for breast cancer incidence. The seven specific risk factors were age (OR: 0.6, 95% CI: 0.53-0.79), first menstrual period (OR: 24; 95% CI: 2.76-207.98), history of tumor (OR: 3.2, 95% CI: 2.28-4.75), long breastfeeding (OR : 95% CI: 2.23-4.54), consumption of fatty foods (OR: 0.2; 95% CI: 0.07-1.00), types of hormonal contraceptives (p value <0 , 05). The result of multivariate analysis with multiple logistic regression was found that menstrual age was the specific factor of a person detected at risk of breast cancer (p value 0.05-0.55) is very important because most women are not aware of breast cancer symptoms and risk factors that are difficult to handle.